2021
DOI: 10.1038/s41586-021-03227-6
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-derived S1P in the lymph node regulates immune responses

Abstract: The lipid chemoattractant sphingosine 1-phosphate (S1P) guides cells from the low-S1P environment of tissues into the high-S1P environment of circulatory fluids( 1 ). Notably, S1P directs T cell exit from lymph nodes (LN), where T cells are initially activated, into lymph, from which T cells reach blood and ultimately inflamed tissues( 1 ). T cells follow S1P gradients primarily using S1P receptor 1 (S1PR1)( 1 ). While recent work has describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 37 publications
3
58
0
Order By: Relevance
“…This argues against the role of endothelial cells for the novel source of S1P. A recent study suggests that inflammatory monocytes secrete S1P during immune responses (Baeyens et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This argues against the role of endothelial cells for the novel source of S1P. A recent study suggests that inflammatory monocytes secrete S1P during immune responses (Baeyens et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, monocytes were reported to provide S1P in lymph nodes in response to inflammation (Baeyens et al, 2021). We explored the possibility that the novel source of S1P is released from myeloid cells.…”
Section: Additional Source Of Plasma S1p From Mx1cre-sensitive Cells May Exist Independent Ofmentioning
confidence: 99%
“…A small trial of fingolimod was initiated with the aim of assessing whether sequestration of lymphocytes via S1PR1 antagonism could reduce postchemoradiation lymphopenia in glioblastoma patients, but have not yet been published (NCT02490930). Interestingly, Baeyens et al recently found that monocytes in the lymph node may also produce S1P and influence T cell differentiation and T cell residence time in the lymph node (152). Their work suggests an alternative mechanism by which drugs that target S1P signaling can influence the glioblastoma TME and immune populations.…”
Section: Altered Phospholipid Metabolismmentioning
confidence: 99%
“…Interestingly, Baeyens et al. recently found that monocytes in the lymph node may also produce S1P and influence T cell differentiation and T cell residence time in the lymph node ( 152 ). Their work suggests an alternative mechanism by which drugs that target S1P signaling can influence the glioblastoma TME and immune populations.…”
Section: Altered Phospholipid Metabolismmentioning
confidence: 99%
“…Recent evidence showed that targeting the S1P/S1PR signaling pathway is crucial for the treatment of immune-mediated diseases (multiple sclerosis and rheumatoid arthritis) [23][24][25], inflammatory bowel diseases [26], lung diseases [27,28], liver diseases [29,30], vascular diseases [31][32][33], brain diseases [34,35], renal diseases [36], and allergy [37]. In the latest clinical trial research, S1P/S1PR also act as a potential new adjuvant therapy to alleviate viral infection of COVID-19 symptoms [38].…”
Section: Introductionmentioning
confidence: 99%